Identifikasi Bakteri Escherichia coli pada Jajanan Kantin Sekolah - Wahyuni, Amalia Dwi; Alza, Yessi; Arsil, Yuliana; Rahayu, Dewi (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2023)
Background: Healthy and safe snacks for consumption are those that can provide benefits and provide energy for the body. Food problems in Indonesia are characterized by cases of food poisoning where food safety is often ignored. The presence of coliform bacteria or Escherichia coli in food is an indicator to determine the level of quality of food and beverages microbiologically. The purpose : To identify the presence of Escherichia coli and coliform bacteria in school canteen snacks. Methods: This research is descriptive qualitative. The samples in this study were flavored ice, cilor, and friedchicken. The test for Escherichia coli and coliform bacteria content using the Total Plate Count (TPC) method was carried out at the UPT Laboratory of Health and Environment of the Riau Provincial Health Office. The results: This study showed that the cilor sample identified the presence of coliform bacteria (100 colonies/g) and fried chicken (50 colonies/g). Then in 3 samples no Escherichia coli bacteria were identified. Conclusion: Coliform bacteria were identified in the snack samples but Escherichia coli bacteria were not identified in the snack samples.